The relationship between stress, social capital and quality of education among medical residents - Charis Anastasiadis; Andreas Tsounis; Pavlos Sarafis (BMC Research Notes, 2018)
Abstract Objective The educational climate is a key factor in medical education. The study aims to examine the relationship between trainee doctors’ perceptions of hospital educational environment, stress and social capital. A cross-sectional study among 104 trainee doctors working in a Greek public hospital was conducted. According to the main hypotheses, perceptions of clinical training are positively associated with social capital and negatively with stress. Results Perceptions of autonomy dimension of training quality was positively related to community participation, tolerance of diversity and total social capital. Perceptions of teaching and social support dimensions of the quality of education were positively correlated with community participation. All training quality subscales were negatively correlated with almost all working stress subscales. Analysis revealed significantly higher scores in autonomy perceptions for those who evaluated their undergraduate studies positively. Females had a significantly lower score in perceptions of teaching and social support scales.